Palaeoscolecids from the Ludlow Series of Leintwardine, Herefordshire ( UK ): the latest occurrence of palaeoscolecids in the fossil record - Howard, RJ; Parry, LA; Clatworthy, I; D'Souza, L; Edgecombe, GD (Wiley, 2024)
The documentation of cuticular micro‐ornament is vital for the taxonomic assignment of palaeoscolecids: vermiform lower Palaeozoic ecdysozoans interpreted as stem‐group priapulans or early diverging panarthropods. This is due to the absence of the character‐rich proboscis and tail hooks in palaeoscolecid material not from Burgess Shale‐type Konservat‐Lagerstätten. Here, the cuticular micro‐ornamentation of palaeoscolecids from the upper Silurian (Ludlow) fauna of Leintwardine (Herefordshire, England), is described using scanning electron microscopy and reflectance transformation imaging. This material is taxonomically unstable because it was included in an effective wastebasket genus (Protoscolex) long before these imaging techniques were developed. The Leintwardine material is shown to be most closely comparable to a palaeoscolecid from the Darriwilian (Middle Ordovician) of the Builth–Llandrindod inlier, Powys, Wales, and is transferred accordingly to Radnorscolex Botting et al. as Radnorscolex latus (Bather). The Leintwardine fauna represents the uppermost stratigraphic occurrence of palaeoscolecids, constrained to the Saetograptus leintwardinensis Zone (lower Ludfordian), and the comparatively sparse Silurian palaeoscolecid record is subsequently discussed. It is hypothesized that palaeoscolecids may have become extinct during the mid‐Ludfordian Lau Event, the onset of which is recorded in the biozone immediately above the Leintwardine fauna (Bohemograptus Zone). Finally, the British palaeoscolecid fauna is summarized, including a new record from the Dapingian (Middle Ordovician) of Carmarthenshire, South Wales.